Regional Differences and Metabolic Changes in Normal Aging of the Human Brain: Proton MR Spectroscopic Imaging Study - Angelie, Emmanuelle; Bonmartin, Alain; Boudraa, Abdel; Gonnaud, Pierre-Marie; Mallet, Jean-Jacques; Sappey-Marinier, Dominique (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Aging is recognized to originate from a diversity of mechanisms that blur the limits between normal and pathologic processes. The purpose of this study was to determine the early effect of normal aging on the regional distribution of brain metabolite concentrations, including N-acetylaspartate (NAA), a major neuronal marker, choline (Cho), and creatine (Cr).METHODS: Thirty-two healthy participants, ages 21 to 61 years, were examined by proton MR spectroscopic (1H MRS) imaging. 1H MRS imaging acquisitions were performed in two brain locations: the centrum semiovale and the temporal lobe. Thirty voxels were selected in four cerebral regions, cortical, semioval, temporal, and hippocampal, and 1H MR spectra were processed to determine the metabolite ratios.RESULTS: With advancing age of the participants, the ratios of %NAA, NAA:Cho, and NAA:Cr were significantly decreased, whereas the ratios of %Cho and %Cr were significantly increased in the cortical, semioval, and temporal regions. On the basis of the significant metabolic difference determined by cluster analysis, two groups of 16 participants with ages ranging from 21 to 39 years (younger group) and 40 to 61 years (older group) were compared. Repeated measures analysis of variance tests, with multiple comparison procedures between the two age groups and among the four brain region groups, showed significant decreases of the %NAA, NAA:Cho, and NAA:Cr ratios in the semioval and temporal regions of the older group compared with the younger group. When compared with other cerebral regions, %NAA and %Cho ratios were significantly decreased in the hippocampal and cortical regions, respectively.CONCLUSION: These metabolic changes suggest that brain aging is characterized by a reduction in neuronal viability or function associated with an accelerated membrane degradation and/or an increase in glial cell numbers.